Numerical Computations : Theory and Algorithms : Third International Conference, NUMTA 2019, Crotone, Italy, June 15–21, 2019, Revised Selected Papers, Part I /: Theory and Algorithms : Third International Conference, NUMTA 2019, Crotone, Italy, June 15–21, 2019, Revised Selected Papers, Part I. (2020) - Unknown
No abstract available